Lasers in gynaecology. (August 2020) - Phillips, Christian; Hillard, Tim; Salvatore, Stefano; Toozs-Hobson, Phil; Cardozo, Linda
Abstract: The use of lasers to treat gynaecological and urogynaecological conditions including genitourinary syndrome of the menopause, stress urinary incontinence, vaginal prolapse and other conditions, has become increasingly popular over recent years. Following widespread concerns over the use of mesh for treating stress urinary incontinence and pelvic organ prolapse and potential adverse outcomes from the use of mesh, there has been heightened awareness and debate over the introduction and adoption of new technologies and interventions within the speciality. On July 30th 2018 the United States Food and Drug Administration (FDA) issued a warning against the use of energy based devices (EBDS) including laser to perform "vaginal rejuvenation" or vaginal cosmetic procedures. Numerous review articles and editorials have urged for greater evidence on the efficacy and safety of vaginal lasers This review outlines the evidence to date for the use of lasers in the treatment of gynaecological conditions.